Towards an Intersectional Understanding of Conflict-Related Sexual Violence: Gender, Sexuality, and Ethnicity at the ICTY - Isaac, Maike (2018)
In the past 25 years, the International Criminal Tribunal for the former Yugoslavia (ICTY) has contributed significantly to a more sophisticated understanding of conflict-related sexual violence (CRSV) in international criminal law. The ICTY’s jurisprudence has broken new ground in relation to the prosecution of CRSV, but also has brought to light the multifaceted challenges associated with the prosecution of such crimes at an international level. Whilst cases heard by the ICTY have addressed both CRSV committed against women and men, there exist significant differences in the ways in which the ICTY has approached the experiences of male victims of sexual violence during the Yugoslav Wars. We therefore analyse the extent to and ways in which the ICTY has fostered the understanding of CRSV as gender-based violence that is embedded into the socio-cultural dynamics of the community within which the violence occurs